Factors associated with the humoral response after three doses of COVID-19 vaccination in kidney transplant recipients - Ángel Bulnes-Ramos; María Mar Pozo-Balado; Israel Olivas-Martínez; Vanesa Garrido-Rodríguez; Gabriel Bernal-Blanco; Alejandro Suárez-Benjumea; Ana Isabel Álvarez-Ríos; Carmen Lozano; Carmen González-Corvillo; Marta Suñer-Poblet; Francisco Manuel González-Roncero; Berta Sánchez; et al. (Frontiers in Immunology, 2023)
IntroductionKidney transplant recipients showed a weak humoral response to the mRNA COVID-19 vaccine despite receiving three cumulative doses of the vaccine. New approaches are still needed to raise protective immunity conferred by the vaccine administration within this group of high-risk patients. MethodsTo analyze the humoral response and identify any predictive factors within these patients, we designed a prospective monocentric longitudinal study of Kidney transplant recipients (KTR) who received three doses of mRNA-1273 COVID-19 vaccine. Specific antibody levels were measured by chemiluminescence. Parameters related to clinical status such as kidney function, immunosuppressive therapy, inflammatory status and thymic function were analyzed as potential predictors of the humoral response. ResultsSeventy-four KTR and sixteen healthy controls were included. One month after the administration of the third dose of the COVID-19 vaccine, 64.8% of KTR showed a positive humoral response. As predictive factors of seroconversion and specific antibody titer, we found that immunosuppressive therapy, worse kidney function, higher inflammatory status and age were related to a lower response in KTR while immune cell counts, thymosin-a1 plasma concentration and thymic output were related to a higher humoral response. Furthermore, baseline thymosin-a1 concentration was independently associated with the seroconversion after three vaccine doses. DiscussionIn addition to the immunosuppression therapy, condition of kidney function and age before vaccination, specific immune factors could also be relevant in light of optimization of the COVID-19 vaccination protocol in KTR. Therefore, thymosin-a1, an immunomodulatory hormone, deserves further research as a potential adjuvant for the next vaccine boosters.